The effect of parental presence on motivation in early childhood language acquisition (Training and Practice : Journal of Educational Sciences, 2021)
“Children tend to enjoy learning and to do better when they are more intrinsically rather than extrinsically motivated to achieve.” (American Society of Psychology, 2019)During my work as a language teacher, I launched language groups for 4-6 year old children several times. As a teacher, it caused a problem for me that there were parents who insisted on the parental presence at the lessons of their children. They used to think, that their presence would encourage their children to acquire as much knowledge as possible during the lessons. I was amazed at this need because I was of the opinion, that the presence of parents at this age already hinders children’s progress among their groupmates and thus affects negatively children’s foreign language acquisition. Therefore, I launched a small sample field research with the participation of two groups of 4-6 year old children. In the case of the first group only children, in the case of the second group their parents also were present in their children's language lessons. During the research, I observed the learning process of the two groups, the behavior and motivation of group members to participate in various activities and measured the increase in knowledge of the two groups.